x^2 - 10x + 24
= x^2 - 4x - 6x + 24
= x(x - 4) - 6(x - 4)
= (x - 6)(x - 4)
ko vt lại đề
x2-6x-4x+24
=(x2-6x)-(4x-24)
=x(x-6)-4(x-6)
=(x-6)(x-4)
\(x^2-10x+24\)
\(\Leftrightarrow x^2-4x-6x+24\)
\(\Leftrightarrow(x^2-4x)-\left(6x-24\right)\)
\(\Leftrightarrow x\left(x-4\right)-6\left(x-4\right)\)
\(\Leftrightarrow\left(x-4\right)\left(x-6\right)\)
Nguyễn Diệu Hoa
phân tích đa thức=> n/tử làm j có dấu tương đương
\(x^2-10x+24\)
\(=x^2-4x-6x+24\)
\(=\left(x^2-4x\right)-\left(6x-24\right)\)
\(=x\left(x-4\right)-6\left(x-4\right)\)
\(=(x-4)\left(x-6\right)\)